ETNOGRAFI KOMUNIKASI DALAM IBADAH SEKOLAH MINGGU HURIA KRISTEN BATAK PROTESTAN (HKBP) MARANATHA KECAMATAN PAYUNG SEKAKI - Artarty Siringoringo; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
HKBP Maranatha Sunday School is one of the church which is devoted to children aged 3-13 years old in Pekanbaru. However, in practice, HKBP Maranatha Sunday School has its own uniqueness that is the use of local languages which is Batak language as the intermediate language. Language became one of the important factors in the implementation of the communication process where the Ethnography of Communication stressed that language can not be separated from how and why the language was used. This study aims to determine the Ethnography of Communication in Sunday School Worship of Huria Kristen Batak Protestant (HKBP) Maranatha District of Payung Sekaki. The purpose of this study was to determine how the communicative situation, communicative events and communicative acts in worship sunday school . The type of research is qualitative. While research method used is an ethnography of communication. Most of the data collected through observation and interviews. Informants in this study were Sunday school chidren, Sunday school teacher and also sintua which selected by using purposive technique. Techniques of collecting data was through interviews, participant observation, and documentation. The results showed that the communicative situation was happened in HKBP Maranatha Sunday school where the situations didn’t conducive because the children didn’t understand the Batak Language. Communicative events based on the type of event that is a religious service. Topics discussed are about the Bible story. The function of using Batak language is to preserve and familiarize the use of Batak language in worship. Setting occurs in HKBP Maranatha held at the end of the month. Participants are sunday school children, Sunday school teacher, sintua and keyboardist. Action communicative is in the form of commands or messages which given by Sunday school teachers to organize the worship, given by sintua to pray and read the Bible and Sunday school children as listener and the implementer.Keywords: Etnography Of Communication, Communicative Situation, Action Communication , Communication Event, Batak Language, Sunday School.